Bài 5
(x-2) (x+2)-x(x-3)=9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a) \(x.\dfrac{3}{4}=\dfrac{9}{14}\)
\(\Rightarrow x=\dfrac{9}{14}:\dfrac{3}{4}\)
\(\Rightarrow x=\dfrac{6}{7}\)
b) \(x:\dfrac{5}{9}=\dfrac{3}{10}\)
\(\Rightarrow x=\dfrac{3}{10}.\dfrac{5}{9}\)
\(\Rightarrow x=\dfrac{1}{6}\)
`a) x(x + 5)(x – 5) – (x + 2)(x^2 – 2x + 4) = 3`
`<=>x(x^2-25)-(x^3-8)=3`
`<=>x^3-25x-x^3+8=3`
`<=>-25x=-5`
`<=>x=1/5`
`b) (x – 3)^3 – (x – 3)(x^2 + 3x + 9) + 9(x + 1)^2 = 15`
`<=>x^3-9x^2+27x-27-(x^3-27)+9(x^2+2x+1)=15`
`<=>-9x^2+27x+9x^2+18x+9=15`
`<=>45x+9=15`
`<=>45x=6`
`<=>x=6/45=2/15`
`c) (x+5)(x^2 –5x +25) – (x – 7) = x^3`
`<=>x^3-125-x+7=x^3`
`<=>x^3-x-118=x^3`
`<=>-x-118=0`
`<=>-x=118<=>x=-118`
`d) (x+2)(x^2 – 2x + 4) – x(x^2 + 2) = 4 `
`<=>x^3+8-x^3-2x=4`
`<=>8-2x=4`
`<=>2x=4<=>x=2`
1.
\(8\times8=64\)
\(6\times4=24\)
\(4\times4=16\)
2.
Ta có:
\(4\times6=24\) \(7\times5=35\)
Vì \(24< 35\) nên \(4\times6< 7\times5\)
Vậy...
_____
Ta có:
\(5\times7=35\) \(8\times9=72\)
Vì \(35< 72\) nên \(5\times7< 8\times9\)
Vậy....
_____
Ta có:
\(3\times5=15\) \(6\times9=54\)
Vì \(15< 54\) nên \(3\times5< 6\times9\)
Vậy...
\(#Wendy.Dang\)
8 x 8 =64
6 x 4 =24
4 x 4=16
Bài 2 : < , > , =
4 x 6 < 7 x 5
5 x 7 < 8 x 9
3 x 5 < 6 x 9
Bài 2:
a: 2/6x5/3=10/18=5/9
b: 11/9x5/10=55/90=11/18
c: 3/9x6/8=1/3x3/4=1/4
d: 4/9x12/16=48/144=1/3
e: 25/15x6/7=5/3x6/7=30/21=10/7
f: 6/10x15/20=90/200=9/20
Bài 1
4/5 x 6/7= 24/35
2/9 x 1/2= 2/18= 1/9
1/2 x 8/3= 8/6= 4/3
7/9 x 6/5= 42/45= 14/15
8/7 x 5/9= 40/63
10/11 x 22/15= 220/165= 4/3
Bài 2
2/6 x 5/3= 1/3 x 5/3=5/9
11/9 x 5/10= 11/9 x 1/2= 11/18
3/9 x 6/8= 1/3 x 3/4 =3/12= 1/4
4/9 x 12/16= 4/9 x 3/4= 12/36= 1/3
25/15 x 6/7= 5/3 x 6/7= 30/21= 10/7
6/10 x 15/20= 3/5 x 3/4= 9/20
a: \(2x+5⋮x+1\)
=>\(2x+2+3⋮x+1\)
=>\(3⋮x+1\)
=>\(x+1\in\left\{1;-1;3;-3\right\}\)
=>\(x\in\left\{0;-2;2;-4\right\}\)
b: \(5x+9⋮x+2\)
=>\(5x+10-1⋮x+2\)
=>\(-1⋮x+2\)
=>\(x+2\in\left\{1;-1\right\}\)
=>\(x\in\left\{-1;-3\right\}\)
c: \(2x+11⋮x+3\)
=>\(2x+6+5⋮x+3\)
=>\(5⋮x+3\)
=>\(x+3\in\left\{1;-1;5;-5\right\}\)
=>\(x\in\left\{-2;-4;2;-8\right\}\)
d: \(4x+9⋮2x+1\)
=>\(4x+2+7⋮2x+1\)
=>\(7⋮2x+1\)
=>\(2x+1\in\left\{1;-1;7;-7\right\}\)
=>\(2x\in\left\{0;-2;6;-8\right\}\)
=>\(x\in\left\{0;-1;3;-4\right\}\)
e: \(6x+7⋮3x+1\)
=>\(6x+2+5⋮3x+1\)
=>\(5⋮3x+1\)
=>\(3x+1\in\left\{1;-1;5;-5\right\}\)
=>\(3x\in\left\{0;-2;4;-6\right\}\)
=>\(x\in\left\{0;-\dfrac{2}{3};\dfrac{4}{3};-2\right\}\)
g: \(10x+13⋮5x+1\)
=>\(10x+2+11⋮5x+1\)
=>\(11⋮5x+1\)
=>\(5x+1\in\left\{1;-1;11;-11\right\}\)
=>\(5x\in\left\{0;-2;10;-12\right\}\)
=>\(x\in\left\{0;-\dfrac{2}{5};2;-\dfrac{12}{5}\right\}\)
\(a,\dfrac{5}{8}=\dfrac{x}{14}\)
\(\Rightarrow x=\dfrac{5.14}{8}=8,75\)
Vậy \(x=8,75\)
\(b,\dfrac{x}{6}=-\dfrac{1}{3}\)
\(\Rightarrow x=-\dfrac{1.6}{3}=-2\)
Vậy \(x=-2\)
\(c,-\dfrac{3}{5}=\dfrac{x}{10}\)
\(\Rightarrow x=-\dfrac{3.10}{5}=-6\)
Vậy \(x=-6\)
câu d đã có đáp án
1) Ta có: \(\left(x+2\right)^2+\left(x-3\right)^2\)
\(=x^2+4x+4+x^2-6x+9\)
\(=2x^2-2x+13\)
2) Ta có: \(\left(4-x\right)^2-\left(x-3\right)^2\)
\(=\left(4-x-x+3\right)\left(4-x+x-3\right)\)
\(=-2x+7\)
3) Ta có: \(\left(x-5\right)\left(x+5\right)-\left(x+5\right)^2\)
\(=x^2-25-x^2-10x-25\)
=-10x-50
4) Ta có: \(\left(x-3\right)^2-\left(x-4\right)\left(x+4\right)\)
\(=x^2-6x+9-x^2+16\)
=-6x+25
5) Ta có: \(\left(y^2-6y+9\right)-\left(y-3\right)^2\)
\(=y^2-6y+9-y^2+6y-9\)
=0
6) Ta có: \(\left(2x+3\right)^2-\left(2x-3\right)\left(2x+3\right)\)
\(=4x^2+12x+9-4x^2+9\)
=12x+18
(x - 2)(x + 2) - x(x - 3) = 9
<=> x2 - 4 - x2 + 3x = 9
<=> -4 + 3x = 9
<=> 3x - 4 = 9
<=> 3x = 9 + 4
<=> 3x = 13
<=> x = 13 : 3
=> x = 13/3